TRANSFORMATIONS IN ECONOMIC ACTIVITIES OF CO-HO PEOPLE IN LAMDONG PROVINCE SINCE RENOVATION TO PRESENT - Lê Minh Chiến; Mai Minh Nhật (Tạp chí Khoa học Đại học Đà Lạt)
This paper presents the transformation in economic activities of Co-ho people in Lamdong province under the influence of the Renovation policy by the Vietnamese Party and State, along with the process of industrialization, modernization, global integration and the local social-economic fluctuations in Lamdong province since 1986. It also analyses the challenges that the people of Co-ho community face concerning their economic development today.